МАСС-МЕДИА И ФИЛОСОФИЯ: ФИЛОСОФСКО- АНТРОПОЛОГИЧЕСКИЙ ДИСКУРС - Мазоренко, М. О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
В статье обобщены основные направления взаимодействия масс-медиа и философии иобоснованы два важнейших тезиса: во-первых, масс-медийное пространство является не толькопредметом философской рефлексии, а и полем формирования философских дискурсовотносительно не масс-медийных стратов общественной и культурной жизни; во-вторых, этидискурсы имеют ясно выраженный философско-антропологический характер.М.О. МазоренкоМАС-МЕДІА І ФІЛОСОФІЯ: ФІЛОСОФСЬКО-АНТРОПОЛОГІЧНИЙ ДИСКУРСУ статті узагальнені основні напрями взаємодії мас-медіа та філософії і обґрунтовані двіважливих тези: по-перше, мас-медійний простір є не тільки предметом філософської рефлексії,але й полем формування філософських дискурсів відносно не мас-медійних стандартів суспільногоі культурного життя; по-друге, ці дискурси мають яскраво виражений філософсько-антропологічний характер.Ключові слова: медіа, медіареальность, філософія, медіафілософія, дискурс, комунікація.M. MazorenkoMEDIA AND PHILOSOPHY: PHILOSOPHICAL-ANTHROPOLOGICAL DISCOURSEThe article generalizes the main directions of the interaction between mass-media and philosophyand two clue teheses have been supplemented: firstly, mass-media space is not only subject forphilosophical reflection but place where philosophical discourses have been formed towards not massmedialstratas of the social and cultural life. Secondly, these discourses have definitely philosophical andanthropological character.Key words: media, a media reality, philosophy, media philosophy, a discourse, communications.